1998
DOI: 10.3171/jns.1998.89.1.0042
|View full text |Cite
|
Sign up to set email alerts
|

Systemic T cell adoptive immunotherapy of malignant gliomas

Abstract: These intriguing clinical observations warrant further trials to determine whether this approach can provide therapeutic benefits and improve survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
123
0
5

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(130 citation statements)
references
References 38 publications
2
123
0
5
Order By: Relevance
“…In this context, it has been documented that four out of 12 patients with newly diagnosed glioma who were treated with adoptive transfer of ex vivo-activated T lymphocytes showed partial regression of the tumour (Plautz et al, 2000). In patients with recurrent malignant gliomas, the local administration of in vitro-expanded tumour-reactive T cells resulted in complete or partial tumour regressions (Tsuboi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it has been documented that four out of 12 patients with newly diagnosed glioma who were treated with adoptive transfer of ex vivo-activated T lymphocytes showed partial regression of the tumour (Plautz et al, 2000). In patients with recurrent malignant gliomas, the local administration of in vitro-expanded tumour-reactive T cells resulted in complete or partial tumour regressions (Tsuboi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy is theoretically appealing because it offers the potential for a high degree of tumor specificity, whereas sparing normal brain structures. Several different laboratories have shown that effective immune responses within the CNS can be generated through the use of gene-modified tumor cell vaccines (2 -4), the adoptive transfer of immune T cells (5,6), or the use of dendritic cell -based vaccines (7 -11). These results imply that systemic immunity can enter the ''immunologically privileged'' CNS, selectively identify tumor-associated antigens, and destroy brain tumor cells (12).…”
mentioning
confidence: 99%
“…Consiste en la inmunización previa del paciente con extracto tumoral (asociado a estimuladores inespecíficos de la inmunidad como BCG o GMCSF), cultivo de linfocitos T activados tras la vacuna y posterior reinfusión de dichos linfocitos. Los resultados obtenidos con estas técnicas tampoco han supuesto un aumento de la supervivencia de los pacientes 36,77 . Kruse y colaboradores 50 han estudiado la posibilidad de emplear linfocitos reactivos frente a proteínas del CMH basándose en la teoría de que estas moléculas se expresan con menor intensidad en neuronas y glía que en células tumorales, habiendo obtenido resultados clínicos prometedores.…”
Section: Inmunoterapia Adoptivaunclassified